The Relationship between Curiosity and Learning Independence of High School Students in Yogyakarta - Fauzan, Parhan; Astuti, Budi; Rachmawati, Indriyana (Jurnal Psikologi Teori dan Terapan, 2026)
Background: This study investigates the relationship between students’ curiosity and their learning independence. Curiosity, as a form of intrinsic motivation, plays a crucial role in encouraging students to explore, question, and engage more deeply in the learning process. Objective: This research examines how students’ curiosity contributes to the development of their learning independence. The research was conducted on 142 grade XI students from a public high school in Yogyakarta using a quantitative correlational approach. Data were collected through validated and reliable questionnaires, with items based on psychological indicators of curiosity and aspects of learning independence. Method: The analysis included validity and reliability testing, normality testing, and Pearson’s Product-Moment correlation. Results: Results show a very strong and statistically significant relationship between curiosity and learning independence (r = 0.976, p < 0.001). Conclusion: These findings suggest that curiosity serves as a foundation for enhancing students’ ability to learn autonomously. The study emphasizes the importance of fostering curiosity as a key strategy to promote self-directed learning and improve overall learning effectiveness. Abstrak Latar Belakang: Penelitian ini menyelidiki hubungan antara rasa ingin tahu siswa dan kemandirian belajar mereka. Rasa ingin tahu, sebagai bentuk motivasi intrinsik, memainkan peran penting dalam mendorong siswa untuk mengeksplorasi, bertanya dan terlibat lebih dalam dalam proses belajar. Tujuan: Penelitian ini bertujuan untuk mengkaji bagaimana rasa ingin tahu siswa berkontribusi terhadap perkembangan kemandirian belajar mereka. Penelitian ini dilakukan terhadap 142 siswa kelas XI dari sebuah sekolah menengah atas negeri di Yogyakarta dengan menggunakan pendekatan korelasional kuantitatif. Data dikumpulkan melalui kuesioner yang telah divalidasi dan diandalkan, dengan item-item yang didasarkan pada indikator psikologis keingintahuan dan aspek-aspek kemandirian belajar. Metode: Analisis meliputi pengujian validitas dan reliabilitas, pengujian normalitas, dan korelasi Moment Produk Pearson. Hasil: Hasil menunjukkan hubungan yang sangat kuat dan signifikan secara statistik antara keingintahuan dan kemandirian belajar (r = 0,976, p < 0,000). Kesimpulan: Temuan ini menunjukkan bahwa keingintahuan berfungsi sebagai fondasi untuk meningkatkan kemampuan siswa dalam belajar secara mandiri. Penelitian ini menekankan pentingnya menumbuhkan keingintahuan sebagai strategi utama untuk mendorong pembelajaran mandiri dan meningkatkan efektivitas pembelajaran secara keseluruhan.